Analysis of the Effect of Lecturer Personal Competency and Teaching Style on Student Learning Achievement in the New Normal Time - Maisura, Maisura; Zakiah, Zakiah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Research "Analysis of the Influence of Lecturer Personality Competence and Teaching Style on Student Achievement in the New Normal Period". The purpose of the research is to find out from this research is to analyze the influence of the lecturer's personality competence and teaching style on student learning achievement in the new normal period. The sample of this study was students of the Faculty of Economics, Jabal Ghafur University. The data analysis technique used simple linear regression analysis to examine the effect of the independent variable X (lecturer's personality competence and teaching style) on the dependent variable Y (student learning achievement). Based on the results of calculated f = 15,768 with a significant level of 0.000 < 0.05, sohypothesis H1 is acceptedit means that there is an effect of the independent variable (X) on the dependent variable (Y). Ptest the value with a significant level of 0.000 <0.05 because the value is greater than the hypothesis is accepted 15thitung=3.971>2.024thitungttabel"> it means that there is an effect of the independent variable (X) on the dependent variable (Y).Score the coefficient of determination (R square) is 0.293, which implies that the effect of the independent variable on the dependent variable is 29.3%. Thus the magnitude of the influence of the lecturer's personality competence on learning outcomes is 29.37% which means it has an influence, while 70.63% is influenced by other factors.